A Review of Price Transparency Policy and Evaluation of Hospital Compliance in Orthopedic Sports Medicine. Issue 2 (July 2021) - Schultz, Kyle; Enterline, Lakai; Igboechi, Oduche; Brahmbhatt, Purav; Hinkley, Jacob; Clement, Carter
Background: In 2019, the Centers for Medicare and Medicaid Services (CMS) announced that beginning January 1, 2021, hospitals would be required to post pricing information in a usable format for patients via diagnosis-related group (DRG) or charge description master (CDM) sheets. Purpose/Questions : We hypothesized the new price transparency rule would pose challenges for many health care facilities. We therefore sought to find out how much pricing information was available before the rule took effect and how usable it was for patients receiving sports medicine care. Methods : In late 2019, we randomly selected 100 general hospitals (GH) from the CMS hospital list and an additional 21 orthopedic hospitals (OH). The DRG and/or CDM sheets were obtained from hospital websites. Pricing information for 6 sports medicine procedures (rotator cuff repair, shoulder arthroscopy, knee arthroscopy, anterior cruciate ligament reconstruction, meniscal repair, and steroid injection) was evaluated in qualitative and quantitative form. Results : Pricing information was provided by 74% of GH and 86% of OH. The price of steroid injections was frequently reported in usable form, with 80% by GH and 78% by OH. The remaining procedures were reported by less than 27% of GH and 40% of OH. For each procedure, component pricing was provided by at least 60% of GH and 78% of OH. No facility provided a pricing calculator or payer-type specific rates. Conclusions : Prior to the enactment of the new price transparency rule in January 2021, most facilities provided some pricing information to patients. However, reporting rates in sports medicine were low and the available data were of little use to patients.